Milyen kockázati tőkés a közép-kelet-európai állam? - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, 2015)
– The entire venture capital sector of Central and Eastern Europe is characterised by the increased weight of state resources. The strengthening of public activities is mainly due to the new type of equity schemes introduced in the European Union's 2007 to 2013 programming period, which allowed the countries in the region to use part of the Structural Funds to develop their venture capital sector. More than 60 venture capital funds undertook to invest more than EUR one billion by the end of 2015, by raising one third of the funds from private investors. The paper examines how successful the CEE EU Member States, with a relatively less developed venture capital industry, were in using government equity schemes based on market cooperation between the state and market actors. Since, due to the shortness of the time elapsed since launching these schemes, the success of the companies financed by such hybrid venture capital funds cannot be assessed, this paper primarily aims to analyse whether the region was able to utilise the past lessons from government equity schemes in countries with a more developed venture capital industry. Similarly to the equity programs applied in the West, the government venture capital programs in the region are also characterised by the short time frame, the mass of administrative requirements tying the hands of investors, the small fund size, which prevents efficient operation, and the limited participation of institutional investors amongst private investors. Compared to developed countries, the unjustified level of benefits to and non-transparent selection of private fund managers and the immaturity of the investment proposals constitute disadvantages in the region. However, the greatest risk of public equity schemes, i.e. the crowding out effect on private investors, is missing in the CEE region due to the lack of market investors.
Keywords: G23; G24; G28; M13; 330; venture capital; government venture capital; government equity schemes; SME finance; Central and Eastern Europe